Novel roles for protein disulphide isomerase in disease states: a double edged sword? - Parakh, Sonam; Atkin, Julie D. (Frontiers in Cell and Developmental Biology, 2015)
Protein disulphide isomerase (PDI) is a multifunctional redox chaperone of the endoplasmic reticulum (ER). Since it was first discovered 40 years ago the functions ascribed to PDI have evolved significantly and recent studies have recognized its distinct functions, with adverse as well as protective effects in disease. Furthermore, post translational modifications of PDI abrogate its normal functional roles in specific disease states. This review focusses on recent studies that have identified novel functions for PDI relevant to specific diseases.